Money, myths, and change: the economic lives of lesbians and gay men - Badgett, Mary Virginia Lee (Worlds of desire, 2001)
How does the standard of living of gay men and lesbians compare with that of heterosexuals? Do homosexuals make financial and family decisions differently? Why are the professional lives of gay men and lesbians dissimilar from those of heterosexuals? Or do they even differ? Have gay people benefited from the recent economic boom? Or have public policies denied them their fair share? Money, Myths, and Change provides new answers to these complex questions. This is the first comprehensive work to explore the economic lives of gays and lesbians in the United States. M. V. Lee Badgett weaves through and debunks common stereotypes about gay privilege, income, and consumer behavior. Studying the ends and means of gay life from an economic perspective, she disproves the assumption that gay men and lesbians are more affluent than heterosexuals, that they inspire discrimination when they come out of the closet, that they consume more conspicuously, that they enjoy a more self-indulgent, even hedonistic lifestyle. Badgett gets to the heart of these misconceptions through an analysis of the crucial issues that affect the livelihood of gay men and lesbians: discrimination in the workplace, denial of health care benefits to domestic partners and children, lack of access to legal institutions such as marriage, the corporate wooing of gay consumer dollars, and the use of gay economic clout to inspire social and political change. Both timely and readable, Money, Myths, and Change stands as a much-needed corrective to the assumptions that inhibit gay economic equality. It is a definitive work that sheds new light on just what it means to be gay or lesbian in the United States.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; capitalisme; cours; discipline; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; shm4000; systèmes d'oppressions; thématiques; travail; états-unis

Lessons from the damned: queers, whores, and junkies respond to AIDS - Stoller, Nancy E. (Routledge, 1998)
"Lessons from the Damned challenges the notion that public health theories and official organizations have the greatest impact on the fight against AIDS. Instead, Stoller looks closely at the ways the most disenfranchised - the poor, people of color, drug users, gay men and lesbians, and women - have built social movements to fight the epidemic. Drawing upon extensive ethnographic research and the words of the activists themselves, as well as the literature of social movements and theories of bureaucracy, Stoller offers guidelines for dealing with diversity and conflict and also with both theoretical and practical perspectives on cross-community and international organizing."--BOOK JACKET.
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; capitalisme; care; cours; discipline; histoire et politique; hétérosexisme; justice sociale; militance; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; sida; soc2014; sociologie; sofia; systèmes d'oppressions; thématiques; états-unis